SOCIO-CULTURAL CONTENT OF HIGH TECHNOLOGIES - Онопрієнко, М. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
We analyze the revolutionary and culturegenic impact of informatsional, cognitive, nano-and biotechnologies upon the social and cultural environment of modern society transformations and the human place in it.